О роли внутрисуставного давления в биомеханике суставов конечностей - Березкин, А.Г. (Вестник зоологии, 1976)
Measurement of intrajoint pressure on the carpal and tarsal joints in various representatives of plantigrades, digitigrades and unguligrades showed that intrajoint pressure may be decreased in one part and increased in the opposite part. Difference in the pressure in different parts of the joint cavity causes constant translocation of synovia, due to which it plays an important role in the demping properties of the joint.